PENGENDALIAN OBESITAS MENURUT STATUS KOMORBID DI MASA PANDEMI COVID-19 - Woro Riyadina; Elisa Diana Julianti; Prisca Petty Arfines; Nuzuliyati Nurhidayati; Irlina Raswanti Irawan; Mohamad Samsudin (Persagi, 2022)
ABSTRACT The trend of obesity continues to increase consistently in Indonesia, even though the government has targeted to maintain the prevalence. Comorbidities play a role in controlling obesity, especially during the COVID-19 pandemic. This study aimed to determine the main determinants of obesity control according to comorbid status during the COVID-19 pandemic. A longitudinal study on 814 cases of obese adults aged 31 years or older who were part of the “Cohort Study of Non-Communicable Disease (NCD) Risk Factors” data in Bogor City. The sample is obese cases (Body Mass Index more or equal to 25 kg/m2) who have complete BMI data before the pandemic (2019) and during the COVID-19 pandemic (2021). The dependent variable was the change in BMI which is defined as the difference (delta) of BMI before and during the COVID-19 pandemic then categorized into three groups (stable, increased, and decreased). The main independent variable was comorbid status which was categorized as healthy, 1 NCD and ≥ 1 NCD). Covariate variables include demographic characteristics, health status (obesity, Common Mental Disorder (CMD), and risk behavior (smoking, length of sitting, exercise, dietary patterns). Data were analyzed by multinomial logistic regression at a significance of p<0.05. During the COVID-19 pandemic, obese cases who were able to control obesity (Stable BMI) at around 36.5 percent and who were able to reduce BMI was 24.6 percent. The main determinant of comorbid to stable BMI was education (OR 2.9 95% CI 1.361 – 6.070, p=0.006), while the determinant of decreased BMI was sitting time for 5.9 hours (OR 1.6 95% CI 1.122– 2.331, p=0.010) after controlling for other factors. Specific nutrition intervention strategies are needed individually, especially for obese cases with low education by considering the health status and increasing physical activity as a healthy lifestyle. Keywords: changes in BMI, control, comorbid, obese, COVID-19 pandemic ABSTRAK Tren obesitas terus meningkat secara konsisten di Indonesia, meskipun pemerintah sudah menargetkan untuk mempertahankan prevalensi obesitas. Komorbid berperan dalam pengendalian obesitas khususnya pada masa pandemi COVID-19. Tujuan studi menentukan determinan utama pengendalian obesitas menurut status komorbiditas di masa pandemi COVID-19. Sebuah studi longitudinal pada 814 kasus obese dewasa umur ≥31 tahun bagian dari data “Studi Kohor Faktor Risiko Penyakit Tidak Menular” di Kota Bogor. Sampel adalah kasus obese (IMT ≥ 25 kg/m2) yang mempunyai data IMT lengkap sebelum pandemi (2019) dan pada masa pandemi COVID-19 (2021). Variabel terikat adalah perubahan IMT yang merupakan selisih (delta) IMT sebelum dan pada masa pendemi COVID-19 dikategorikan menjadi tiga kelompok (stabil, turun dan naik). Variabel bebas utama adalah status komorbid yang dikategorikan menjadi sehat, 1 PTM dan ≥ 1 PTM. Variabel kovariat meliputi karakteristik demografi, status kesehatan (obesitas, gejala mental emosional (GME), perilaku berisiko: merokok, lama duduk, olahraga, pola konsumsi). Data dianalisis dengan regresi logistik multinomial pada signifikansi p< 0,05. Selama masa pandemi COVID-19, kasus obese yang mampu mengendalikan obesitas (IMT Stabil) 36,5 persen dan mampu menurunkan IMT sebesar 24,6 persen. Determinan utama hubungan komorbid dengan IMT stabil adalah pendidikan (OR 2,9 95% CI 1,361 – 6,070, p=0,006) sedangkan determinan utama perubahan IMT turun adalah lama duduk ≤ 5,9 jam (OR 1,6 95% CI 1,122– 2,331, p=0,010) setelah mengontrol faktor lain. Diperlukan strategi intervensi gizi yang spesifik secara individual, khususnya bagi kasus obese dengan tingkat pendidikan rendah dengan mempertimbangkan status sehat (tanpa komorbid) dan peningkatkan aktivitas fisik sebagai gaya hidup sehat. Kata kunci: perubahan IMT, kendali, komorbid, obesitas, pandemi COVID-19